2013
DOI: 10.1177/193229681300700217
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Control Hyperglycemia in NonCritically Ill Diabetes Patients despite Standard Glycemic Management in a Hospital Setting

Abstract: The recommended BG target range was not achieved in both wards. Analysis of routine glycemic management demonstrated considerable glycemic management effort, but also a lack of translation into adequate insulin therapy. Implementation of corrective measures, such as structured treatment protocols, is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
0
15
0
4
Order By: Relevance
“…1,15 These trends of suboptimal glucose control are seen even when speciality input is available. 16 In our study, time within the recommended target glucose range was increased by closed-loop insulin delivery by roughly 22% compared with a matched cohort receiving usual care. This outcome was achieved without an increase in the amount of insulin delivered, thereby further minimising the risk of hypoglycaemia.…”
Section: Discussionmentioning
confidence: 60%
“…1,15 These trends of suboptimal glucose control are seen even when speciality input is available. 16 In our study, time within the recommended target glucose range was increased by closed-loop insulin delivery by roughly 22% compared with a matched cohort receiving usual care. This outcome was achieved without an increase in the amount of insulin delivered, thereby further minimising the risk of hypoglycaemia.…”
Section: Discussionmentioning
confidence: 60%
“…The controlled study was conducted at two general wards at the Department of Internal Medicine (Medical University of Graz, Austria). At both wards a recently performed study found comparable and sustained BG levels around 10.0 mmol/l in diabetic patients independent of antihyperglycaemic treatments . In this study, algorithm‐based treatment was implemented at one ward and compared to standard glycaemic management at the other ward.…”
Section: Methodsmentioning
confidence: 95%
“…In a study of 3000 hospitalized patients, Moreira et al [5] report 52% of patients on the wards and 61% of patients in the intensive care unit on RISS alone. Other similar but smaller studies corroborate this, reporting 64-75% use of RISS alone [6,8,9]. Small prospective RCTs have demonstrated the superiority of basal-bolus insulin therapy vs RISS in medical and surgical inpatients [2,10].…”
mentioning
confidence: 57%
“…Nevertheless, the use of RISS still remains prevalent. While it is difficult to accurately gauge its world-wide use, recent reports from Spain [4], Brazil [5], Austria [6] and Malaysia [7] attest to its embeddedness in clinical practice. When examined carefully, the high frequency of RISS only use in hospitalized patient is astounding.…”
mentioning
confidence: 99%